Normal values of respiratory oscillometry in South African children and adolescents - Chaya Shaakira; MacGinty Rae; Jacobs Carvern; Githinji Leah; Hlengwa Sipho; Simpson Shannon J.; Zar Heather J.; Hantos Zoltán; Gray Diane M. (2023)
Introduction Noninvasive measurement of respiratory impedance by oscillometry can be used in young children aged from 3 years and those unable to perform forced respiratory manoeuvres. It can discriminate between healthy children and those with respiratory disease. However, its clinical application is limited by the lack of reference data for African paediatric populations. The aim of the present study was to develop reference equations for oscillometry outcomes in South African children and adolescents. Methods Healthy subjects, enrolled in the Drakenstein Child Health Study, HIV-uninfected adolescents in the Cape Town Adolescent Antiretroviral Cohort and healthy children attending surgical outpatient clinics at Red Cross War Memorial Children's Hospital were measured with conventional spectral (6-32 Hz) and intra-breath (10 Hz) oscillometry. Stepwise linear regression was used to assess the relationship between respiratory variables and anthropometric predictors (height, sex, ancestry) to generate reference equations. Results A total of 692 subjects, 48.4% female, median age of 5.2 years (range: 3-17 years) were included. The median (interquartile range (IQR)) for weight for age z-score and height for age z-score was -0.42 (-1.11-0.35) and -0.65 (-1.43-0.35), respectively. Stepwise regression demonstrated that all the variables were significantly dependent on height only. Comparison to previous reference data indicated slightly higher resistance and lower compliance values in the smallest children. Conclusion We established the first respiratory oscillometry reference equations for African children and adolescents, which will facilitate use in early identification and management of respiratory disease. Our results suggest differences in oscillometry measures by ancestry but also highlight the lack of standardisation in methodology.
Keywords: Klinikai orvostan